PERILAKU KEUANGAN IBU PEKERJA: KAJIAN EMPIRIS DENGAN MODEL MODERASI FAKTOR SOSIAL DAN EKONOMI - Nuraeni Hadiati Farhani; Dini Ayuning Ratri Sukimin; Asterina Anggaraini; Azzriel Rafi Handoko; Grasela Lasria Anatalia (Politeknik Negeri Ambon, 2026)
Introduction: The dual role of women is increasingly prominent, with female labor force participation reaching 54.42% and around 14.37% of them being female breadwinners. In urban areas such as Bandung City, a dynamic economic condition requires good financial planning skills to maintain family welfare. Financial literacy is an important factor in shaping healthy financial behavior, but its effectiveness can be influenced by husband support. This study aims to analyze the effect of financial literacy on the financial planning behavior of working mothers with husband support as a moderating variable and income adequacy as a control variable. Methods: This study uses a quantitative approach with a survey method. Data were collected through the distribution of questionnaires to 100 working mother respondents in Bandung City. The analysis technique used is (PLS-SEM).Results: The research results show that financial literacy has a positive effect on the financial planning behavior of working mothers. Husband support strengthens this relationship, while income adequacy also contributes positively, confirming the importance of the synergy between financial capability, partner support, and economic stability in shaping healthy financial behavior. Keywords: Financial Literacy, Financial Planning Behavior, Income, Husband Support, Working Mothers